Gene Structure Analysis of Chemokines and Their Receptors in Allotetraploid Frog, Xenopus laevis - Fukui, Akimasa; Matsunami, Masatoshi (Frontiers in Genetics, 2022)
Chemokines, relatively small secreted proteins, are involved in cell migration and function in various biological events including immunity, morphogenesis, and disease. Due to its nature, chemokines tend to be a target of hijacking of immunity by virus and therefore show an exceptionally high mutation rate. Xenopus laevis is considered an excellent model to investigate the effect of whole-genome duplication for gene family evolution. Because its allotetraploidization occurred around 17-18 million years ago, ancestral subgenomes L and S were well conserved. Based on the gene model of human and diploid frog Xenopus tropicalis, we identified 52 chemokine genes and 26 chemokine receptors in X. laevis. The retention rate of the gene in the X. laevis L and S subgenome was 96% (45/47) and 68% (32/47), respectively. We conducted molecular phylogenetic analysis and found clear orthologies in all receptor genes but not in the ligand genes, suggesting that the mutation rate remarkably increased in the ligand. dN/dS calculation demonstrated that dN/dS rate greater than 1 was observed in the four ligand genes, cxcl8a.S, cxcl18.S, ccl21.S, and xcl1.L, but nothing in receptor genes. These results revealed that the whole genome duplication promotes diversification of chemokine ligands in X. laevis while conserving the genes necessary for homeostasis, suggesting that selective pressure also supports a rapid evolution of the chemokines in amphibians.